ACCELERATION RENDERING METHOD ON RAY TRACING WITH ANGLE COMPARISON AND DISTANCE COMPARISON - liliana, Liliana; Adipranata, Rudy (Institute of Research and Community Outreach - Petra Christian University, 2007)
In computer graphics applications, to produce realistic images, a method that is often used is ray tracing. Ray tracing does not only model local illumination but also global illumination. Local illumination count ambient, diffuse and specular effects only, but global illumination also count mirroring and transparency. Local illumination count effects from the lamp(s) but global illumination count effects from other object(s) too. Objects that are usually modeled are primitive objects and mesh objects. The advantage of mesh modeling is various, interesting and real-like shape. Mesh contains many primitive objects like triangle or square (rare). A problem in mesh object modeling is long rendering time. It is because every ray must be checked with a lot of triangle of the mesh. Added by ray from other objects checking, the number of ray that traced will increase. It causes the increasing of rendering time. To solve this problem, in this research, new methods are developed to make the rendering process of mesh object faster. The new methods are angle comparison and distance comparison. These methods are used to reduce the number of ray checking. The rays predicted will not intersect with the mesh, are not checked weather the ray intersects the mesh. With angle comparison, if using small angle to compare, the rendering process will be fast. This method has disadvantage, if the shape of each triangle is big, some triangles will be corrupted. If the angle to compare is bigger, mesh corruption can be avoided but the rendering time will be longer than without comparison. With distance comparison, the rendering time is less than without comparison, and no triangle will be corrupted.